Workload and Workplace Well-being of Junior High School Teachers: Their Implications to NAT Performance of Grade 10 Students - Villamayor, Mercidita Sendaydiego; Sayson, Shaunell Mary Josol; Castillon, Hannah Tuyor (FKIP Universitas Lampung, 2023)
Workload and Workplace Well-being of Junior High School Teachers: Their Implications to NAT Performance of Grade 10 Students. Objectives: This research examined Grade 10 students' 2017-2018 NAT performance, explored junior high school teachers' workload and workplace well-being, and investigated the relationship between workload, workplace well-being, and NAT performance. Methods: Descriptive-correlational designs were used, utilizing BEA data and survey questionnaires on workload and workplace well-being administered to junior high school teachers in Malaybalay and Valencia Cities. Findings: Grade 10 students' 2017-2018 NAT performance was low proficient, and junior high school teachers reported heavy workloads but high workplace well-being. No significant relationships were found between NAT performance and workload or workplace well-being. Conclusion: Grade 10 students' 2017-2018 NAT performance presented a challenge. Teachers reported heavy workloads but high workplace well-being. Other factors may affect student performance, requiring further investigation to enhance educational outcomes.Keywords: grade 10 students, nat, workload, workplace well-beingDOI: http://dx.doi.org/10.23960/jpp.v13.i3.202301